1994
DOI: 10.4141/cjps94-041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of propiconazole application on foliar disease and yield of irrigated spring wheat in Saskatchewan from 1990 to 1992

Abstract: al. 1990). The present study was conducted to determine the optimal time for application ofpropiconazole on spring wheat to control S. nodorumand other foliar diseases in order to achieve maximum yield benefit in the Outlook irrigation area of Saskatchewan. All tests were carried out at the Irrigation Development Centre, Outlook, Saskatchewan on land which grew wheat for at least the previous two years. In the spring, 100 kg ha-l of 34-0-0 fertilizer was broadcast before seeding.During the growing season, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Bockus et al (1997) found the optimum timing to be between the boot and the fully headed growth stages. Duczek and Jones-Flory (1994) found the optimum timing to be between extension of the flag leaf and the medium milk growth stages. Wiersma and Motteberg (2005) found that across cultivars, the optimum timing for foliar fungicide application was ZGS 60 rather than ZGS 39.…”
Section: Discussionmentioning
confidence: 99%
“…Bockus et al (1997) found the optimum timing to be between the boot and the fully headed growth stages. Duczek and Jones-Flory (1994) found the optimum timing to be between extension of the flag leaf and the medium milk growth stages. Wiersma and Motteberg (2005) found that across cultivars, the optimum timing for foliar fungicide application was ZGS 60 rather than ZGS 39.…”
Section: Discussionmentioning
confidence: 99%
“…Bockus et al (1997) found the optimum timing to be between the boot and the fully headed growth stages. Duczek and Jones-Flory (1994) found the optimum timing to be between extension of the flag leaf and the medium milk growth stages. Wiersma and Motteberg (2005) found that across cultivars, the optimum timing for foliar fungicide application was GS 60 rather than GS 39.…”
Section: Timing Of Foliar Fungicide Application In Winter Wheatmentioning
confidence: 99%
“…Many studies have reported that these diseases have a negative effect on grain yield (Eyal and Ziv 1974;King et al 1983;McKendry and Henke 1994), kernel weight (Morris et al 1989;Gooding et al 1994), test weight (Milus 1994), grain protein concentration (Clare et al 1993) and milling quality (McKendry et al 1995), especially under environments favorable for disease development, or under intensive management practices such as irrigation (Duczek and Jones-Flory 1994) and high rates of N fertilizer (Howard et al 1994). However, some studies have shown that yields and seed characteristics were not consistently affected by leaf spotting diseases (Shtienberg et al 1990;Peltonen and Karjalainen 1992;Stover et al 1996).…”
mentioning
confidence: 99%